Study of a Methodology for Calculating Contact Stresses during Blade Processing of Structural Steel; Metals; Vol. 13, iss. 12 - Kozlov V. N. Victor Nikolayevich; Babaev A. S. Artem Sergeevich; Shults N. A. Nikita Aleksandrovich; Semenov A. V. Artem Valerjevich; Shevchuk A. S. Anton Sergeevich (2023, 2023)
Title screen